2022
DOI: 10.21037/atm-22-192
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of type 2 diabetes mellitus to hypothalamic inflammation and depressive disorders in young patients with obesity

Abstract: Background: To explore the contribution of type 2 diabetes mellitus (T2DM) to hypothalamic inflammation and depressive disorders in young patients with obesity.Methods: According to the diagnostic criteria for T2DM, all of patients with obesity were divided into the diabetic and the non-diabetic groups. The severity of depressive disorders was assessed by self-rating depression scale (SDS). The signal intensity (SI) ratio of the T2-weighted phase of the superior hypothalamus/ amygdala (H/A) was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…More than ½ of patients with type 2 diabetes mellitus having obstructive sleep apnea [ 60 ], with sleep apnea contributing to weight gain and visceral fat accumulation [ [61] , [62] , [63] ]. Diabetes-related inflammation are interrelated with obesity [ 64 ], with diabetes being potentially associated with hypothalamic inflammation [ 65 ], which in turn is also linked to promoting obesity [ 66 , 67 ]. Diabetes-related eye disease [ 68 ] , kidney disease [ 69 ] , and skin disease (i.e., diabetes foot ulcer) [ 70 ] may impair physical activity, thus potentially impair weight reduction effectiveness.…”
Section: Potential Mechanisms For Impaired Weight Reduction Among Pat...mentioning
confidence: 99%
“…More than ½ of patients with type 2 diabetes mellitus having obstructive sleep apnea [ 60 ], with sleep apnea contributing to weight gain and visceral fat accumulation [ [61] , [62] , [63] ]. Diabetes-related inflammation are interrelated with obesity [ 64 ], with diabetes being potentially associated with hypothalamic inflammation [ 65 ], which in turn is also linked to promoting obesity [ 66 , 67 ]. Diabetes-related eye disease [ 68 ] , kidney disease [ 69 ] , and skin disease (i.e., diabetes foot ulcer) [ 70 ] may impair physical activity, thus potentially impair weight reduction effectiveness.…”
Section: Potential Mechanisms For Impaired Weight Reduction Among Pat...mentioning
confidence: 99%
“…With the continuous improvements in the quality of life of the population, it is expected that there will be more than one billion people with diabetes globally by 2030, and more than 90 million patients will have diabetic retinopathy (4). The development of diabetes is closely related to the inflammatory response (5). Researchers have found increased levels of inflammatory factors such as interleukin-1β (IL-1β) and interleukin-6 (IL-6) in aqueous humor and serum of patients with diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that elevated FBG was an independent predictor of depressive disorder in young patients with obesity. 31 And we further found that higher FBG level was associated with a higher risk of depression in T2DM patients (OR: 1.06, 95% CI: 1.00–1.11).…”
Section: Discussionmentioning
confidence: 51%